(untitled) (Research, Society and Development, 2023)
According to IBGE´s 2015 data, the population segment that most increases in the Brazilian population is the elderly. In 2030, the number of elderly people will surpass that of children and adolescents. The multiple associated comorbidities, which usually result in the phenomenon of polypharmacy, such as modified pharmacokinetics and the natural cognitive decline of this group, result in low adherence to therapy, the worsening of clinical conditions and increased health costs, being an important challenge to be overcome. In order to describe the main tools and strategies related to the promotion of therapeutic adherence in the elderly described in the literature, an integrative bibliographic review was carried out, in which they were analyzed regarding their possibility of application as a guide for the pharmaceutical service in a School Pharmacy. This methodology resulted in the pointing out of some strategies that are already being carried out in a school pharmacy, where interventions designed for long-term care generally require continuous work, and the integrated application of more tools provides greater chances of therapy success. In this case, the pharmacist is the most capable professional to provide this assistance, especially when inserted in an educational environment.